2009
DOI: 10.1007/s10600-009-9312-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of essential oils from leaves of Rhododendron dauricum and R. aureum

Abstract: Rhododendron dauricum L. and R. aureum Georgi. (Ericaceae) are medicinal plants used in Tibetan medicine to treat several pathological conditions [1]. Phenolic and terpenoid compounds have been observed previously in these plants [2]. In addition, the compositions of essential oils of both species growing in Russia (Khabarovsk Territory [3], Amur [4], Irkutsk Oblast, Buryatiya [5]) and in China [6] have been reported. Our goal was to study the dynamics of essential oil (EO) composition change of leaves of R. d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…This chemical constituent found was however different from the studies on other Rhododendron species: the main components of R. nivale essential oil were δ-cadinene and α-cadinol [9]. Furthermore, studies on essential oils from leaves of R. dauricum and R. aureum revealed that the major chemical constituents were trans-caryophyllene and calarene, respectively [10]. And β-pinene, camphene and δ-3-carene were the major constituents of the oil of R. mucronulatum [11].…”
Section: A Chemical Composition Of Essential Oilcontrasting
confidence: 68%
“…This chemical constituent found was however different from the studies on other Rhododendron species: the main components of R. nivale essential oil were δ-cadinene and α-cadinol [9]. Furthermore, studies on essential oils from leaves of R. dauricum and R. aureum revealed that the major chemical constituents were trans-caryophyllene and calarene, respectively [10]. And β-pinene, camphene and δ-3-carene were the major constituents of the oil of R. mucronulatum [11].…”
Section: A Chemical Composition Of Essential Oilcontrasting
confidence: 68%
“…Furthermore, studies on essential oils from leaves of R . dauricum and R. aureum found that the dominant compounds were trans -caryophyllene and calarene, respectively [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The latter comprises some 100-125 genera and more than 3,000 species [ 36 ] that are, generally speaking, poorly studied in respect to volatile metabolites. Table 2 lists the Ericaceae taxa whose essential oils were previously chemically analyzed using a methodology comparable to that applied in this work [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Compositional data on the essential oils of the species listed in Table 2 (28 samples in total) were mutually compared by means of multivariate statistical analyses (MVA: AHC and PCA).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the aim of this work was set to analyze in detail (using GC and GC/MS) and compare the chemical composition of the essential oils hydrodistilled from the dry leaves of A. uva-ursi and V. vitis-idaea , in order to determine if any further phytochemical similarities between the two species exist. Comparison of the compositional data of the oils from a number of Ericaceae taxa (present study and the literature data [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]) was achieved using multivariate statistical analyses (MVA: agglomerative hierarchical cluster analysis (AHC) and principal component analysis (PCA)).…”
Section: Introductionmentioning
confidence: 99%